Explicit Motor Imagery for Grasping Actions in Children With Spastic Unilateral Cerebral Palsy - Errante, Antonino; Bozzetti, Francesca; Sghedoni, Silvia; Bressi, Barbara; Costi, Stefania; Crisi, Girolamo; Ferrari, Adriano; Fogassi, Leonardo (Frontiers in Neurology, 2019)
Background: Motor Imagery (MI) refers to mental simulation of a motor action without producing any overt movement. Previous studies showed that children with Unilateral Cerebral Palsy (UCP) are impaired in implicit MI, as demonstrated by the performance of Hand Laterality Judgment tasks. The aim of this study was to examine the specificity of explicit MI deficits in UCP children. Methods: A group of UCP children (n = 10; aged 9 to 14) performed a mental chronometry task consisting in grasping an object and placing it into a container, or in imagining to perform the same action. As control, a group of typically developing (TD) children, matched by age, performed the same task. Movement durations for executed and imagined trials were recorded. A subgroup of 7 UCP children and 10 TD children also underwent a session of functional MRI to examine the activation of parieto-frontal areas typically associated to MI processes, during the imagination of reaching-grasping actions performed with the paretic hand. Results: Behavioral results revealed the existence of a correlation between executed and imagined movement durations both in TD and UCP groups. Moreover, the regression analysis in TD children showed that higher scores in mental chronometry tasks were positively correlated to increased bilateral activation of the intraparietal sulcus (IPS), superior parietal lobule (SPL) and dorsal premotor (PMd) cortex. A similar analysis revealed in UCP group a positive correlation between higher score in the mental chronometry task and bilateral activations of IPS and to activation of contralesional, right PMd and putamen during imagination of grasping movements. Conclusions: These results provide new insights on the relationship between MI capacity and motor deficits in UCP children, suggesting the possibility of the use of explicit MI training to improve patient’s upper limb motor functions.